2005
DOI: 10.1007/s10888-005-9001-9
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and the reproduction of economic inequality in polarized societies

Abstract: inequality, social capital, social collateral, socio-economic polarization., Z130 – Social Norms and Social Capital, O–Economic Development, Technological Change, and Growth.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…This captures the notion that for many poor people, social networks do not provide a viable escape route from long-term poverty, as Mogues and Carter (2005) and Adato et al ). This latter subgroup's first-best arrangement proves socially infeasible, leaving them worse off than they might have been under a different equilibrium social network configuration, but still able to exit poverty in time.…”
Section: The Possibilities Presented By Social Network and Their Limmentioning
confidence: 57%
See 1 more Smart Citation
“…This captures the notion that for many poor people, social networks do not provide a viable escape route from long-term poverty, as Mogues and Carter (2005) and Adato et al ). This latter subgroup's first-best arrangement proves socially infeasible, leaving them worse off than they might have been under a different equilibrium social network configuration, but still able to exit poverty in time.…”
Section: The Possibilities Presented By Social Network and Their Limmentioning
confidence: 57%
“…3 For example, Adato et al (2006), Mogues and Carter (2005) and Santos and Barrett (2006), among others. 4 See, for example, the recent volumes by Barrett (2005) and Bowles et al (2006) and the December 2005 special issue of the Journal of Economic Inequality on "Social Groups and Economic Inequality".…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some have defined groups as being collections of individuals whose transactions/contacts within group are significantly greater than their transactions outside the group (Blau, 1977). This effect has been modelled by Lundberg and Startz (1998) and Mogues and Carter (2005), while Durlauf (2000) shows how 'neighbourhood' effects can sustain poverty, via peer group effects, social learning and social complementarities. An empirical investigation into neighbourhoods in the US found that neighbourhood effects influence intergenerational mobility, while ethnic factors play an additional role even among people who grow up in the same neighbourhood (Borjas, 1995).…”
Section: A Framework For Considering the Evolution Of Hismentioning
confidence: 99%
“…For example, Tilly has made important contributions on both fronts, mainly considering the US situation (Tilly, 1998). Recent work by Mogues and Carter, (2005) has considered theoretical issues, this time with a greater focus on developing countries, while there have been a number of empirical studies with bearing on the 1 We are grateful to Graham Brown and Luca Mancini for helpful comments on a previous draft.…”
Section: Introductionmentioning
confidence: 99%
“…We especially seek to provide a theoretical foundation for the quite mixed empirical effects of social network capital on poor households' well-being. While some empirical studies -e.g., Narayan and Pritchett (1999) -find that social network capital effectively serves as a substitute for real capital in mediating economic mobility in many economies, others, such as Adato et al (2006) and Mogues and Carter (2005), suggest that accumulation of social network capital proves ineffective for households at the bottom of the economic pyramid in highly 1 Examples include Loury (1981), Banerjee and Newman (1993), Galor and Zeira (1993), Dercon (1998), and Ray (2002, 2003). See Azariadis and Stachurski (forthcoming) or Carter and Barrett (2006) for helpful reviews of key threads in the poverty traps literature.…”
Section: Introductionmentioning
confidence: 99%